1999
DOI: 10.1021/la990186j
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependence of the Stability of Emulsion Drops Pressed against a Large Interface

Abstract: In this work we study experimentally the lifetime of oil droplets pressed by buoyancy against a large oil/water interface, in a system containing protein (bovine serum albumin). The stability of the drops depends strongly on their size, which can be explained with the hydrodynamics of thinning of the gap region. Two distinct size intervals with different thinning regimes may be discerned: (i) Very small drops (below ∼20 µm). They remain practically nondeformed up to coalescence; in this case the lifetime dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 16 publications
7
80
0
Order By: Relevance
“…Jones and Wilson [12] is an important theoretical work on the film drainage problem of a drop over a plane interface, which shows the importance of interface mobility and the narrowing of the film at its periphery (the so-called dimple). Finally, the work of Basheva et al [13] showed experimentally for the first time the dependence of the coalescence time on drop diameter in a wide range where two distinct coalescence regimes have been predicted: a Taylor regime for very small drops where there is no drop deformation and the film lifetime decreases with drop diameter (lubrication regime), and a Reynolds regime for large drops where there is drop deformation and the film lifetime increases with drop diameter (independently of the interface mobility). As a result, the coalescence time as a function of drop diameter passes through a minimum.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Jones and Wilson [12] is an important theoretical work on the film drainage problem of a drop over a plane interface, which shows the importance of interface mobility and the narrowing of the film at its periphery (the so-called dimple). Finally, the work of Basheva et al [13] showed experimentally for the first time the dependence of the coalescence time on drop diameter in a wide range where two distinct coalescence regimes have been predicted: a Taylor regime for very small drops where there is no drop deformation and the film lifetime decreases with drop diameter (lubrication regime), and a Reynolds regime for large drops where there is drop deformation and the film lifetime increases with drop diameter (independently of the interface mobility). As a result, the coalescence time as a function of drop diameter passes through a minimum.…”
Section: Introductionmentioning
confidence: 94%
“…We can then mention the works of Hartland [7][8][9][10], Hodgson and Lee [11], Jones and Wilson [12] and Basheva et al [13]. In Hartland [7][8][9], although there are no results on coalescence times, other aspects of drop/interface coalescence have been studied in detail such as the drop shape when resting on a plane interface, the variation of film thickness with time and radial position and the film retraction.…”
Section: Introductionmentioning
confidence: 99%
“…Most of this theoretical and experimental research has been done for single droplets coalescing with a planar surface (e.g. Aryafar and Kavehpour, 2006;Basheva et al, 1999;Bozzano and Dente, 2011;Charles and Mason, 1960;Dickinson et al, 1988;Hartland, 1967aHartland, , 1967bHartland, , 1967cHool et al, 1998;Jeffreys and Hawksley, 1965;Kourio et al, 1994;Mackay and Mason, 1963;Mohamed-Kassim and Longmire, 2004;Ortiz-Duenas et al, 2010;Thoroddsen, 2006). Extensive theoretical research Postprint: Kamp, J.…”
mentioning
confidence: 99%
“…According to recent emulsion stability simulations (ESS) an approximate threshold for drop deformation occurs around 2.5 µm [56,57,63,64]. Drops with radii smaller than 2.5 µm will mostly behave as non-deformable particles.…”
Section: Flocculation Of Oil Dropsmentioning
confidence: 99%